Financial Institutions Management : a Risk Management Approach / Anthony Saunders, Marcia Millon Cornett - Saunders, Anthony
Saunders and Cornett's Financial Institutions Management: A Risk Management Approach provides an innovative approach that focuses on managing return and risk in modern financial institutions. The central theme is that the risks faced by financial institutions managers and the methods and markets through which these. risks are managed are becoming increasingly similar whether an institution is chartered as a commercial bank, a savings bank, an investment bank, or an insurance company. Although the traditional nature of each sector's product activity is analyzed, a greater emphasis is placed on new areas. of activities such as asset securitization, off-balance-sheet banking, and international banking.